An overview of capability evaluation of Measurement Systems and Gauge Repeatability and Reproducibility Studies - ŞENVAR, ÖZLEM; FIRAT, SENİYE ÜMİT (My University, 2010)
This study is an overview of the capability evaluation of measurement systems. Principally, the determination of capability of a measurement system is an important aspect of quality and process improvement initiatives. In practice, various methods are developed and used for determining measurement system capability. As a measurement tool, potential effectiveness of gauge should be considered and significant factors should be identified for that purpose. A set of procedures referred to as Measurement Systems Capability Studies are conducted for assessing capability of gauge, isolating sources of variability in the system, evaluating how much of total observed variability is due to gauge, and investigating two components of measurement error: repeatability and reproducibility of gauge. Gauge Repeatability & Reproducibility (Gauge R&R) Study tries to estimate repeatability and reproducibility components of measurement system variation with primary objective of assessing whether gauge is suitable for intended application or not. Measurement System Analysis (MSA) is a collection of statistical methods, which includes Gauge R&R Study, for analysis of measurement system capability. In this study, detailed literature review of MSA, Gauge R&R and Measurement Systems Capability Studies, and general discussion of misclassification probabilities that give useful, reliable information about measurement systems performance would be provided. © EDP Sciences 2010.
Keywords: Gauge Repeatability and Reproducibility (Gauge R&R); Measurement System Analysis (MSA); Measurement Systems Capability Studies